Ecstasy Use among U.S. Adolescents from 1999 to 2008 - Wu, Ping (2010)
AIMS: To investigate trends in rates of ecstasy use among US adolescents from 1999 to 2008, and to examine the associations between the major sociodemographic factors, especially gender, and ecstasy use, during this period. METHODS: The adolescent subsamples (ages 12–17) from the 1999–2008 NHSDA/NSDUH surveys were used for the current study. Data from adolescents’ self–reports on use of ecstasy and of other drugs, as well as sociodemographic characteristics, were used in the analyses. RESULTS: There was an increasing trend in adolescent ecstasy use from 1999 to 2002, which was followed by a decreasing trend from 2002 to 2005, and a slight rise from 2005 to 2008. In contrast to some other drugs, ecstasy was more likely to be used by girls than by boys. This gender difference persisted over the 10-year period and could not be explained by other demographic factors. CONCLUSION: Given the known health consequences of ecstasy use, especially for females, the observed gender difference in adolescent ecstasy use should be taken into account by drug prevention and intervention programs.